Ribosomal DNA ITS-1 intergenic spacer polymorphism in triatomines (Triatominae, Heteroptera) - Tartarotti, E.; Ceron, C. R. (Springer, 2005)
The length polymorphism of ribosomal DNA ITS-1 intergenic spacer was analyzed in eight species of triatomines belonging to Triatoma, Rhodnius, and Panstrongylus genera. The analyzed species were Rhodnius domesticus, R. neivai, R. robustus, Triatoma brasiliensis, T. infestans, T. vitticeps, Panstrongylus megistus, and P. herreri. These insects are vectors of Chagas' disease, one of the most prominent public health problems among South American countries. This work allowed the differentiation between species of the Triatomini and Rhodniini tribes through the analysis of ITS-1 length polymorphism by PCR and RFLP techniques. The species of the Triatoma and Panstrongylus genera presented an amplified ITS-1 fragment between 600 and 1000 bp, whereas Rhodnius presented a less variable ITS-1 length fragment, around 300 bp, which could reflect the monophyletic origin of the Rhodniini tribe. Species belonging to this genus were further differentiated by RFLP with HaeIII and AluI endonucleases. Our results corroborate the hypothesis of polyphyletic origin in this group of insects and contribute to knowledge about evolutionary relationships in triatomines.
Keywords: triatomines; Triatominae; ITS-1 (intergenic spacer); rDNA